2018
DOI: 10.1186/s12933-017-0651-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial extracellular volume assessed by cardiovascular magnetic resonance T1 mapping and its determinants in type 2 diabetes mellitus patients with normal myocardial systolic strain

Abstract: BackgroundCardiac magnetic resonance (CMR) T1 mapping and tissue-tracking strain analysis are useful quantitative techniques that can characterize myocardial tissue and mechanical alterations, respectively, in patients with early diabetic cardiomyopathy. The purpose of this study was to assess the left ventricular myocardial T1 value, extracellular volume fraction (ECV), and systolic strain in asymptomatic patients with type 2 diabetes mellitus (T2DM) and their underlying relationships with clinical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 51 publications
(79 reference statements)
2
38
0
Order By: Relevance
“…As has been demonstrated in previous studies in humans [33, 34], ECV values in monkeys with T2DM were elevated. The use of T1ρ contrast to assess myocardial fibrosis has been reported in several swine studies in which T1ρ values as much as doubled in the myocardial scar tissue as compared with the normal tissue [10, 13].…”
Section: Discussionsupporting
confidence: 84%
“…As has been demonstrated in previous studies in humans [33, 34], ECV values in monkeys with T2DM were elevated. The use of T1ρ contrast to assess myocardial fibrosis has been reported in several swine studies in which T1ρ values as much as doubled in the myocardial scar tissue as compared with the normal tissue [10, 13].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, in a recent population-based study, the extracellular volume fraction was found to be reduced in T2D patients [51]. It has been suggested that antihypertensive medication, especially angiotensin-converting enzyme (ACE) inhibitors, may regress myocardial fibrotic remodeling in response to hypertension [52]. Our South Asian but not European T2D study population had an increased LV mass, paralleled by a reduced extracellular volume fraction.…”
Section: Discussionmentioning
confidence: 73%
“…Traditional SSFP cine sequences (bFFE, TrueFISP, and FIESTA) are suitable for CMR tissue tracking and only require a relatively quick and easy post-processing approach making these sequences ideal for the quantitative evaluation of LV myocardial strain characteristics. Presently, few studies are focusing on the assessment of myocardial strain damage using CMR tissue tracking in T2DM patients 18 . Thus, in the present study, we aimed to quantify myocardial strain using CMR tissue tracking, in T2DM patients, especially in patients with preserved LVEF, and to determine the ability of myocardial strain parameters to assessment the LV deformation.…”
Section: Introductionmentioning
confidence: 99%